In Silico Study of Splicing Variations on Angiotensin-Converting Enzyme 2 (ACE2) and Its Effects on Infection from SARS-CoV-2 - Ihsan Fauzan (Indonesian Society for microbiology, 2023)
Several factors can influence SARS-CoV-2 infection. Alternative Splicing is thought to correlate with the differences of affinity value for interactions with the SARS-CoV-2 spike protein so that the infection may be influenced. This phenomenon can be happened by generating various kinds of protein expression variations with different isoform variants. So far, the difference in interaction affinity with the SARS-CoV-2 spike protein in Alternative Splicing has not been widely reported. Therefore, this study aimed to determine the isoform resulting from Alternative Splicing in the ACE2 transcript and its effect on SARS-CoV-2 infection. Molecular docking was used to determine the binding affinity between ACE2 proteins isoforms and SARS-CoV-2 spike protein. The 3D protein model of ACE2 isoforms obtained from the database was validated by evaluating the model quality of each ACE2 isoform. Based on docking results, there are variations in the docking scores of 8 isoform variants. However, there was no interaction between the ACE2_205 variant and SARS-CoV-2 spike protein while ACE2_206 and ACE2_207 showed a lower docking score than the other variants. In addition, essential residues in the interaction of each variant were also analyzed. Q42 and A384 are residues on the ACE2 protein that appear in interactions in more than two variants. These results indicate the possibility that splicing variations can cause differences in a person's level of susceptibility to SARS-CoV-2 infection, especially in the ACE2_205 variant that cannot interact with the SARS-CoV-2 spike protein.